Nicotinic acetylcholine receptors mediate lung cancer growth - Improgo, Ma. Reina; Soll, Lindsey G.; Tapper, Andrew R.; Gardner, Paul D. (Frontiers in Physiology, 2013)
Ion channels modulate ion flux across cell membranes, activate signal transduction pathways, and influence cellular transport—vital biological functions that are inexorably linked to cellular processes that go awry during carcinogenesis. Indeed, deregulation of ion channel function has been implicated in cancer-related phenomena such as unrestrained cell proliferation and apoptotic evasion. As the prototype for ligand-gated ion channels, nicotinic acetylcholine receptors (nAChRs) have been extensively studied in the context of neuronal cells but accumulating evidence also indicate a role for nAChRs in carcinogenesis. Recently, variants in the nAChR genes CHRNA3, CHRNA5, and CHRNB4 have been implicated in nicotine dependence and lung cancer susceptibility. Here, we silenced the expression of these three genes to investigate their function in lung cancer. We show that these genes are necessary for the viability of small cell lung carcinomas (SCLC), the most aggressive type of lung cancer. Furthermore, we show that nicotine promotes SCLC cell viability whereas an α3β4-selective antagonist, α-conotoxin AuIB, inhibits it. Our findings posit a mechanism whereby signaling via α3/α5/β4-containing nAChRs promotes lung carcinogenesis.